Impact of Position in Family on Suicide: A Case-Control Psychological Autopsy Study among Chinese Rural Youths - Zhou, Qin; Li, Ning; Zhang, Jie; Fan, Libo (Depression and Anxiety, 2023)
Introduction. Suicide remains an important public health issue in China. Existing literature on the relationship between individual-familial variables and suicide risk mainly focused on family socioeconomic status, and few studies analyzed the effect of position in family on suicide. In this study, we aimed to explore the association between position in family and suicide among Chinese rural youths. Methods. We conducted a case-control psychological autopsy study. The data collection yielded 392 suicide cases aged 15-34 years and 416 community living controls within the same age range. Personal position in family was assessed by the question “How do you evaluate his/her position in the family?” and categorized as high, general, and low to reflect the relative position in family. Logistic regression models were conducted to explore the association between position in family and suicide risk. Results. The results showed that compared with females (males) having a high position in family, females (males) with a low position in family were 7.1 (9.1) times more likely to commit suicide (p<0.01). Mental disorders, social support, and coping strain were potentially important mediating factors linking position in family to suicide, with certain heterogeneity among males and females. Low coping strain played the most important role in underlying the association between a low position in family and suicide for both females and males, accounting for 55% (28%) of the contribution to the total effect for females (males). Subgroup analysis revealed that low position in family had more significant impacts on suicide risk among married youths and those with low education levels. Conclusion. The effect of position in family on suicide should receive greater consideration when predicting suicide in rural China. Possible mechanisms underlying the effect of position in family on suicide include mental status, social support, and coping strain.